CHALLENGES FACED BY STUDENTS ON WRITING SKILLS IN ESL CONTEXTS - Mohamed, Rashin Hasan. (IJRDO- Journal of Educational Research, 2022)
English is an international language and in demand today. Some of the challenges that are faced by the ESL students are lack of vocabulary, poor grammar, poor spelling, students’ readiness and lack of exposure to books and reading materials. The challenges faced by the students’ have made it challenging teachers to teach writing skills. English is by far the most widely used language around the world. However, English language writing has always been a challenge for second language students to master. Developing students’ ability in writing is one of the major challenges faced by the ESL teachers in most schools nowadays. Nevertheless, writing has always been a major difficulty faced by students in English language learning, especially in elementary schools. Not only that, teachers are also facing some challenges in teaching writing skills for students in elementary schools. Thus, this study aims to explore the challenges faced by both the students and teachers in learning as well as teaching writing skills in elementary schools.